SEXUALLY TRANSMITTED DISEASES: THE PERCEPTION OF ADOLESCENTS IN A STATE SCHOOL - Fabrine Aguilar Jardim; Thamara de Souza Campos; Renan Neves da Mata; Maria da Penha Rodrigues Firmes (Universidade Federal do Paraná, 2013)
This descriptive study with a qualitative approach sought to investigate the adolescents' perception regarding sexually transmitted diseases. Interviews were held with 30 adolescents from a state school in Diamantina, Minas Gerais, between August and December 2012. The interviews were transcribed and underwent the process of identification of the nuclei of meaning and categorization by Content Analysis, two categories emerging: Knowledge of sexually transmitted diseases and Ways of acquiring information on sexually transmitted diseases. The condom represented the main form of prevention, and the risks caused to health and social life were death, AIDS and prejudice. The adolescents converse with friends/class-mates, and the actions in relation to these diseases were experienced through lessons and presentations. The adolescents' perception regarding sexually transmitted diseases contributes to re-thinking the importance of projects, further studies and public policies for reducing vulnerability and behaviors of risk during the experience of sexuality in adolescence.